Analysis of students' proportional reasoning in solving story problems - Husain, Asrianti; Ikram, Muhammad; Bahri, Fahrul; Tanak, Akio (International Journal of Progressive Mathematics Education, 2023)
The purpose of this qualitative research is to analyze students' proportional reasoning in solving word problems. The research instrument is a proportional reasoning task sheet for comparison material that has been validated. The subjects of this study were 20 students of grade VII junior high school. The data collection procedure begins with students working on research instruments to determine students' proportional reasoning abilities. After working on the proportional reasoning task sheet, interviews were conducted to find out the students' proportional reasoning, then 3 research subjects were selected to be interviewed with a level of proportional reasoning that fulfills the character namely: (1) building relationships between quantities, (2) writing down quantity ratios to present problems , (3) stimulate to make multiplicative relationships; and (4) looking for unknown values. Data analysis techniques in this study were carried out by transcribing the verbal data collected and reviewing all available data from various sources, namely student answers, think alouds, and interviews. The results of the study obtained 3 subjects from class VII SMP indicating that from the description and analysis of the subjects the researcher found was holistic proportional reasoning.   Tujuan penelitian kualitatif ini adalah untuk menganalisis penalaran proporsional siswa dalam menyelesaikan soal cerita. Instrumen penelitian ini berupa lembar tugas penalaran proporsional materi perbandingan yang telah divalidasi. Subjek penelitian ini adalah siswa kelas VII SMP yang berjumlah 20 siswa. Prosedur pengumpulan data diawali dengan siswa mengerjakan instrumen penelitian untuk mengetahui kemampuan penalaran proporsional siswa. Setelah mengerjakan lembar tugas penalaran proporsional, wawancara dilakukan untuk mengetahui penalaran proporsional yang dimiliki siswa, kemudian dipilih 3 subjek penelitian untuk diwawancarai dengan tingkat penalaran proporsional yang memenuhi karakter yakni: (1) membangung hubungan antar kuantitas, (2) menuliskan kuantitas rasio untuk mempresentasikan masalah, (3) menstimulasikan untuk membuat hubungan multiplikatif; dan (4) mencari nilai yang tidak diketahui.Teknik analisis data dalam penelitian ini dilakukan dengan mentranskripkan data verbal yang dikumpulkan dan meninjau semua data yang tersedia dari berbagai sumber yaitu jawaban siswa, think alouds, dan wawancara. Hasil penelitian diperoleh 3 subjek dari kelas VII SMP menunjukkan bahwa dari deskripsi dan analisis subjek yang peneliti temukan adalah penalaran proporsional tipe holistik